2012
DOI: 10.1111/j.1447-0349.2011.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Models of case management for working with young children: Implications for mental health nurses

Abstract: The care of children with behavioural disorders/mental illnesses is an important and emerging role for mental health nurses. Unfortunately, there is little evidence on which to base their practice. Children, because of their rapid emotional, physical, and cognitive development, and their dependence on their families, need special consideration in their mental health care. The limited evidence available indicates that this special consideration should include a focus, not only on the child, but also on the pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…) which means that mental health nurses can offer family‐centred care, advice and education to other professionals and teachers (Browne et al . ). Staff turnover needs to be addressed as consistency is a critical requirement for adolescents (Harper et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) which means that mental health nurses can offer family‐centred care, advice and education to other professionals and teachers (Browne et al . ). Staff turnover needs to be addressed as consistency is a critical requirement for adolescents (Harper et al .…”
Section: Discussionmentioning
confidence: 97%
“…Hildegard Peplau (1952) emphasized the therapeutic relationship and engagement with the person as critical for humanistic person-centred care. The focus on person rather than the problem, therapeutic use of self and the therapeutic relationship are central tenets in mental health nursing practice today (Barker 2009, Morrissey & Callaghan 2011, Browne et al 2014 which means that mental health nurses can offer family-centred care, advice and education to other professionals and teachers (Browne et al 2012). Staff turnover needs to be addressed as consistency is a critical requirement for adolescents (Harper et al 2013).…”
Section: Implications For Practicementioning
confidence: 99%
“…According to the National Board (2004b), health talks by school nurses developed a special form of support and a health-promotion approach, based on individual strengths and weaknesses, which is in line with the results of the study. The results of the study showed that the school used various tools when working with schoolchildren’s mental health in which health talks were an important tool ( Browne et al, 2012 ). During the health talks, school nurse used bear cards, for example, that helped the child express various emotions.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted by Hepworth, Rooney and Rooney (2013:410), "case management as a stand-alone practice method or when integrated with another treatment approach has demonstrated its effectiveness in addressing a range of needs or problems of specific populations". Browne, Cashin and Graham (2012) analysed three studies on case management models that focused on mental health service delivery in schools. In these models teachers and families collaborated in the provision of services to facilitate the achievement of positive psychological and educational outcomes (Browne et al, 2012).…”
Section: Programme-based Case Management Systemmentioning
confidence: 99%
“…Browne, Cashin and Graham (2012) analysed three studies on case management models that focused on mental health service delivery in schools. In these models teachers and families collaborated in the provision of services to facilitate the achievement of positive psychological and educational outcomes (Browne et al, 2012). Sandberg, Jakobsson and Kristensson (2014) explored the experiences of service providers and receivers using case management models for frail older people.…”
Section: Programme-based Case Management Systemmentioning
confidence: 99%